2010
DOI: 10.1071/wr09046
|View full text |Cite
|
Sign up to set email alerts
|

Predator-baiting experiments for the conservation of rock-wallabies in Western Australia: a 25-year review with recent advances

Abstract: Abstract. Predation is widely believed to be the main threatening process for many native vertebrates in Australia. For 25 years, predator-baiting experiments have been used in the Western Australian Central Wheatbelt to control red fox predation on rock-wallabies and other endangered marsupial prey elsewhere. We review here the history of a series of baiting experiments designed to protect rock-wallaby colonies by controlling red foxes with 1080 poison baits. We continue to support the conclusion that red fox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…Moreover, by undertaking applied-science experiments which circumvent investigations of the internal processes at play and instead focus on the actual in situ prey responses to top-predator control (R6 in Figure 1) -what Kinnear et al [74] label the 'black box' approach -our results confirm that prey populations are typically unaffected by contemporary dingo control practices independent of how predators and prey might interact with each other (R2 in Figure 1). …”
Section: Trophic Cascade and Mesopredator Release Theory And Realitysupporting
confidence: 65%
“…Moreover, by undertaking applied-science experiments which circumvent investigations of the internal processes at play and instead focus on the actual in situ prey responses to top-predator control (R6 in Figure 1) -what Kinnear et al [74] label the 'black box' approach -our results confirm that prey populations are typically unaffected by contemporary dingo control practices independent of how predators and prey might interact with each other (R2 in Figure 1). …”
Section: Trophic Cascade and Mesopredator Release Theory And Realitysupporting
confidence: 65%
“…There remains, however, limited reliable data on the longer term and indirect effects of dingo control faunal biodiversity [41,85]. Investigating R6 is a 'black box' approach to applied research [86], meaning the observed outcomes of control interventions can enable management progress in the absence of a complete understanding of the mechanisms responsible for the outcomes. For example, [86] summarised the results of 25 years of experimental research on the conservation of threatened black-footed rock-wallabies Petrogale lateralis, stating that researchers had found time and again that fox control resulted in more rock-wallabies, but they did not have a good grasp on the mechanisms responsible for it.…”
Section: Knowledge Gaps In the Literaturementioning
confidence: 99%
“…Investigating R6 is a 'black box' approach to applied research [86], meaning the observed outcomes of control interventions can enable management progress in the absence of a complete understanding of the mechanisms responsible for the outcomes. For example, [86] summarised the results of 25 years of experimental research on the conservation of threatened black-footed rock-wallabies Petrogale lateralis, stating that researchers had found time and again that fox control resulted in more rock-wallabies, but they did not have a good grasp on the mechanisms responsible for it. Thus, if investigations of R6 show that threatened prey populations fluctuate independently of dingo control, lethal control of dingoes might continue to occur without concern from conservationists that such practices inhibit the recovery of threatened fauna through trophic effects.…”
Section: Knowledge Gaps In the Literaturementioning
confidence: 99%
“…Boundaries may be defined by capitalising on semi-permeable habitat barriers (e.g. Zalewski et al 2009;Fraser et al 2013), but buffer areas with a degree of invasive species control have also been used effectively (Thomson et al 2000;Kinnear et al 2010). Because non-ecological factors such as availability of financial resources and the protection designation of land masses often define management areas (e.g.…”
Section: Introductionmentioning
confidence: 99%